ENHANCING CREATIVE PERFORMANCE: THE ROLE OF ETHICAL LEADERSHIP, WORK ENGAGEMENT, AND POSITIVE EMOTIONS - Faheem Ahmad Khan; Muhammad Umer Quddoos; Ammara Akram; Muhammad Adeel (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2024)
The pharmaceutical industry is undergoing fast change, and one key factor influencing organizational success and salesperson performance is the leadership style of field managers. This study assesses how ethical leadership style affects central salespersons’ outcomes like positive emotions, work engagement, and creative performance. This study focused on the theoretical and conceptual literature on focal variables. Seven hypotheses were developed to explain how ethical leadership style drives salesperson outcomes in Pakistan’s pharmaceutical industry. A sample of 350 pharmaceutical medical representatives from 30 national and multinational firms was used to evaluate the relationships between the selected variables using SPSS-25.00 and AMOS-22.0. Pharmaceutical companies can benefit from the study’s findings in various ways like establishing ethical leadership standards among field managers to enhance creative performance. Investing in programs that foster ethical leadership skills can result in more engaged salespeople with higher creative performance. Limitations and future directions are also discussed.